Experimental and Thermodynamic Study on new CO2 absorbents - Zhou Mengyue; Liu Yubing; Li Hongwei; Tang Zhigang; Xing Xiao; Guo Dong; Fei Weiyang (Carbon Capture Science & Technology, 2022)
UNIFAC model is a thermodynamic model for predicting activity coefficients based on the group contribution method, which is very important in predicting gas-liquid equilibrium, especially for CO2-absorbent system. In this research, we used UNIFAC model to regress the interaction parameters of -CH2O versus CO2, -CH2O versus -CO3 in CO2-1, 2-Dimethoxyethane and Dimethyl Carbonate-1, 2-Dimethoxyethane system through experimental and literature data, and predicted the increased solubility of CO2 in the absorbents with increased number of ether bonds and carbon chain. Results revealed the Henry's coefficient of CO2 in CO2- Dimethyl Carbonate system is 1.32 and 1.42 times higher than that in CO2-pentane-3-oxy-1,5-diyl dimethyl dicarbonate and CO2- octane-3,6-dioxy-1,8-diyl dimethyl dicarbonate system at 323.15K, respectively. The gas-liquid equilibrium results calculated by UNIFAC model correspond well with experimental results. This study provides a new idea for designing CO2 new absorbent.